Peer review of third trimester abdominal circumference measurements - Dyer, Ellen (Ultrasound, 2020)
BACKGROUND: Third trimester growth scans represent a significant proportion of the workload in obstetric ultrasound departments. The objective of these serial growth scans is to improve the antenatal detection of babies with fetal growth restriction. The aim of this paper is to describe a method of peer review for third trimester abdominal circumference measurements which is realistic within busy obstetric ultrasound departments in the UK. METHOD: Twenty-two, third trimester, measured abdominal circumference images were randomly selected. Images were assessed subjectively by 12 sonographers using the image Criteria Achieved Score. For quantitative assessment, termed the Inter-operator Variability Score, three of the abdominal circumference (AC) images were blindly remeasured. Following this, a questionnaire was used to ascertain which image criteria sonographers considered most important and to reach an agreement on correct caliper placement. RESULTS: The least frequently met image criteria with the lowest Criteria Achieved Score related to an oblique abdominal circumference section. These included fetal kidney present (Criteria Achieved Score 24.6%), multiple oblique ribs (Criteria Achieved Score 39.4%) and oblique spine (Criteria Achieved Score 37.5%). Caliper placement was also identified as inconsistent. DISCUSSION: This study demonstrates that the perfect AC section is not always possible and sonographers use their professional judgement to determine whether an image is acceptable. Seventy-three percent of the images reviewed were of an acceptable standard. There can be inconsistencies in sonographer opinion regarding what is an acceptable third trimester abdominal circumference image. These differences need to be addressed to maximise the effectiveness of the third trimester ultrasound examination. CONCLUSION: Peer review can be used to monitor scan quality and identify areas of inconsistency.